Perlindungan Hukum Terhadap Anak Pada Kasus Eksploitasi Anak: Studi Kasus: Eksploitasi Demi Sabu Di Aceh - Saskia Azzahra; Audrey Chandra; Tri Widiya Sari; Irenna Rusydanti (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
The high level of exploitation of children is an issue that requires serious attention. In Indonesia itself, child exploitation is one of the social problems that must be resolved by all groups, both government and society. Many cases of exploitation of children occur to be used as street buskers not requested by others but from the closest people, namely parents. Basically, every human being has basic rights that need to be protected, not only for adults, but also for children. Parents should be the main figure and place to get protection in fulfilling the rights of children. The method used in writing this article is normative legal research method, which is research based on literature study and legal literature related to child protection. The conclusion of this article is that the government and authorized institutions as well as the community need to conduct more in-depth socialization to all Indonesian people so that people understand about child exploitation recognize actions that lead to child exploitation and the importance of increasing a sense of concern for children who are victims of economic exploitation and a sense of caring for others.